Adaptação e validação de um instrumento de avaliação dos pés de pessoas com diabetes mellitus - COSTA, Saulo Pereira da (2016)
Diabetes Mellitus (DM) is a multiple etiology syndrome that triggers severe complications, one of the most common being diabetic foot. In order to guide the clinical nursing practice, assisting in decision-making on foot care, this study aimed at developing an assessment tool for the feet of people with diabetes and verify their metric properties. This is a methodological research, developed in three stages: Stage I, preparation of the instrument, called IAP-DM in this study; stage II, characterized by apparent and content validation; and stage III, verify the validity of the criteria and instrument reliability. For criterion validity, we used the Pearson's (r) and Spearman's (ρ) correlation coefficient. To test reliability, the internal consistency the areas that make up the IAP-DM (Cronbach's alpha) was evaluated, and its reproducibility with inter-evaluation, using simple Kappa and weighted Kappa, besides the intraclass correlation coefficient (ICC) to the overall scores obtained in relation to the observations of the researchers. The significance level adopted was 0.01. The apparent and content validation were relevant and indicate that the items were included in the evaluation of the judges. The instrument was applied to 131 people with DM in the period between June and August 2016,in three Family Health Units from Uberaba- MG. Of the sample, 51.1% were women, 70.2% elderly, 77.1% had Hypertension. Eight areas (75%) showed high internal consistency (α> 0.70). Most of the compliance of the instrument items (79.2%) was classified as almost perfect (K = .81 to .99), the ICC value obtained was 0.99 and 0.98 for MID and MIE evaluation scores respectively, which indicates excellent reliability. Criterion validity identified a positive correlation of strong magnitude (r = 0.78 and ρ = 0.69 for MID, r = 0.81 and ρ = 0.69 for the MIE and p <0.001), considered very significant. The results indicate that the instrument of this study is valid and reliable. Although consistent values of validity and reliability for the IAP-DM tool have been identified, it is recommended that further studies are carried out in order to pursue a cutoff point for the diagnosis of neuropathic and vascular complications, using for such the receiver operating characteristic (ROC curve).